Visualization and quantification of transition metal atomic mixing in Mo(1−x)W(x)S(2) single layers - Dumcenco, Dumitru O (Nature Pub. Group, 2013)
The alloying behaviour of materials is a well-known problem in all kinds of compounds. Revealing the heteroatomic distributions in two-dimensional crystals is particularly critical for their practical use as nano-devices. Here we obtain statistics of the homo- and heteroatomic coordinates in single-layered Mo(1−x)W(x)S(2) from the atomically resolved scanning transmission electron microscope images and successfully quantify the degree of alloying for the transition metal elements (Mo or W). The results reveal the random alloying of this mixed dichalcogenide system throughout the chemical compositions (x=0 to 1). Such a direct route to gain an insight into the alloying degree on individual atom basis will find broad applications in characterizing low-dimensional heterocompounds and become an important complement to the existing theoretical methods.